Pengaruh Metode Kangguru Terhadap Peningkatan Berat Badan Pada BBLR Diruang Perina RSKD Duren Sawit Tahun 2023 - Wanti Wanti; Nurul Ainun Shifa (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Introduction: Low birth weight babies are babies weighing <2500 grams. Babies with LBW tend to experience hypothermia and infection, so an effort needs to be made to prevent this, one of which is by using the KMC method. Kangaroo Mother Care is a treatment for low birth weight babies that involves making direct contact between the baby's skin and the mother's skin.Objective: This study aims to determine the effect of the kangaroo method on weight gain in LBW babies at Duren Sawit RSKD.Method: This research is a quasi-experimental quantitative study with a pretest- posttest one-group design. The sample in this study consisted of 20 babies with LBW who were selected using a purposive sampling technique. The instruments in this study were KMC management SOPs and observation sheets. Data collection was carried out 2 times, namely before being given the KMC method and after being given the KMC method. Data processing using the SPSS computer program using the Wilcoxon analysis test. Results: Most of the mothers were aged 20–35 years, namely 11 people (55.0%), and most of the babies were female, namely 12 people (60.0%). Before being given the kangaroo method, all babies experienced low birth weight, where the baby's weight was in the minimum BB category, namely <2500 grams for 20 people (100.0%). After being given the kangaroo method, most of the babies with LBW had a weight in the normal weight category, namely ≥2500 grams, as did as many as 12 people (60.0%). The results of the Wilcoxon test analysis show a p-value of 0.001, which means that there is an effect of the KMC method on increasing LBW weight at the Durem Sawit Hospital in 2023. Conclusion: There is an effect of the KMC method on increasing LBW weight at the Durem Sawit Hospital in 2023.